Virulence gene profiles and antimicrobial susceptibility of Salmonella Brancaster from chicken - Khoo, Evie; Roslee, Roseliza; Zakaria, Zunita; Ahmad, Nur Indah (Korean Society of Veterinary Science, 2023)
Background: The current conventional serotyping based on antigen-antisera agglutination could not provide a better understanding of the potential pathogenicity of Salmonella enterica subsp. enterica serovar Brancaster. Surveillance data from Malaysian poultry farms indicated an increase in its presence over the years. Objective: This study aims to investigate the virulence determinants and antimicrobial resistance in S. Brancaster isolated from chickens in Malaysia. Methods: One hundred strains of archived S. Brancaster isolated from chicken cloacal swabs and raw chicken meat from 2017 to 2022 were studied. Two sets of multiplex polymerase chain reaction (PCR) were conducted to identify eight virulence genes associated with pathogenicity in Salmonella (invasion protein gene [invA], Salmonella invasion protein gene [sipB], Salmonella-induced filament gene [sifA], cytolethal-distending toxin B gene [cdtB], Salmonella iron transporter gene [sitC], Salmonella pathogenicity islands gene [spiA], Salmonella plasmid virulence gene [spvB], and inositol phosphate phosphatase gene [sopB]). Antimicrobial susceptibility assessment was conducted by disc diffusion method on nine selected antibiotics for the S. Brancaster isolates. S. Brancaster, with the phenotypic ACSSuT-resistance pattern (ampicillin, chloramphenicol, streptomycin, sulphonamides, and tetracycline), was subjected to PCR to detect the corresponding resistance gene(s). Results: Virulence genes detected in S. Brancaster in this study were invA, sitC, spiA, sipB, sopB, sifA, cdtB, and spvB. A total of 36 antibiogram patterns of S. Brancaster with a high level of multidrug resistance were observed, with ampicillin exhibiting the highest resistance. Over a third of the isolates displayed ACSSuT-resistance, and seven resistance genes (β-lactamase temoneira [blaTEM], florfenicol/chloramphenicol resistance gene [floR], streptomycin resistance gene [.strX], aminoglycoside nucleotidyltransferase gene [ant(3')-Ia], sulfonamides resistance gene [sul-1, sul-2], and tetracycline resistance gene [tetA]) were detected. Conclusion: Multidrug-resistant S. Brancaster from chickens harbored an array of virulence-associated genes similar to other clinically significant and invasive non-typhoidal Salmonella serovars, placing it as another significant foodborne zoonosis. © 2023 The Korean Society of Veterinary Science This is an Open Access article distributed under the terms of the Creative Commons Attribution NonCommercial License (https://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited.